Climate Humanities in the L2 Classroom: Radical Possibilities for an Uncertain Future - Aguilo Mora, Francisca; Marín Cobos, Almudena (Radical Teacher, 2025)
This article explores the current politics and practices of language teaching and learning at higher education in the US, and the ethical dilemmas that we face as instructors of Spanish as a Second Language (L2) with a focus on climate emergency. How can we teach and learn Spanish—a colonial language mostly in Latin America, but also in Africa, Asia, and even Oceania—in the context of climate and the environment without somehow perpetuating the ‘colonial normal’? How can we teach and learn Spanish in the context of climate and the environment without somehow propagating the colonial imperative? If we acknowledge that the climate crisis is the result of intersectional colonial and neocolonial processes at various levels, we need to decolonize our teaching dynamics. Thus, to tackle these questions, we propose radical curricular possibilities for advancing diversity, equity, and inclusion in the L2 classroom with a focus on climate and sustainability. Our teaching philosophy proposes a root-level transformation and delves around the following teaching principles: contextualization of language teaching, critical analysis and decentralization of climate discourse, shared expertise and active learning, and transdisciplinarity.